Bone Morphogenetic Protein 9 Protects Against Myocardial Infarction by Improving Lymphatic Drainage Function and Triggering DECR1-Mediated Mitochondrial Bioenergetics - Duan, Zikun; Huang, Zhouqing; Lei, Wei; Zhang, Ke; Xie, Wei; Jin, Hua; Wu, Maolan; Wang, Ningrui; Li, Xiaokun; Xu, Aimin; Zhou, Hao; Wu, Fan; et al. (Circulation (New York, N.Y.), 2024)
BACKGROUND: BMP9 (bone morphogenetic protein 9) is a member of the TGF-β (transforming growth factor β) family of cytokines with pleiotropic effects on glucose metabolism, fibrosis, and lymphatic development. However, the role of BMP9 in myocardial infarction (MI) remains elusive. METHODS: The expressional profiles of BMP9 in cardiac tissues and plasma samples of subjects with MI were determined by immunoassay or immunoblot. The role of BMP9 in MI was determined by evaluating the impact of BMP9 deficiency and replenishment with adeno-associated virus-mediated BMP9 expression or recombinant human BMP9 protein in mice. RESULTS: We show that circulating BMP9 and its cardiac levels are markedly increased in humans and mice with MI and are negatively associated with cardiac function. It is important to note that BMP9 deficiency exacerbates left ventricular dysfunction, increases infarct size, and augments cardiac fibrosis in mice with MI. In contrast, replenishment of BMP9 significantly attenuates these adverse effects. We further demonstrate that BMP9 improves lymphatic drainage function, thereby leading to a decrease of cardiac edema. In addition, BMP9 increases the expression of mitochondrial DECR1 (2,4-dienoyl-CoA [coenzyme A] reductase 1), a rate-limiting enzyme involved in β-oxidation, which, in turn, promotes cardiac mitochondrial bioenergetics and mitigates MI-induced cardiomyocyte injury. Moreover, DECR1 deficiency exacerbates MI-induced cardiac damage in mice, whereas this adverse effect is restored by the treatment of adeno-associated virus-mediated DECR1. Consistently, DECR1 deletion abrogates the beneficial effect of BMP9 against MI-induced cardiomyopathy and cardiac damage in mice. CONCLUSIONS: These results suggest that BMP9 protects against MI by fine-tuning the multiorgan cross-talk among the liver, lymph, and the heart.